(untitled) (World Bulletin of Social Sciences, 2022)
This article is devoted to the research of materials on the tax system of the Khiva Khanate in the “Turkistan collection”. Khiva Khanate reveals the scientific significance of the “Turkistan collection” consisting of articles published in the press about tax types, administration, taxable objects and their scale, tax collection process and officials who will lead it